2009
DOI: 10.1016/j.antiviral.2009.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity of the hemolymph of Lonomia obliqua (Lepidoptera: Saturniidae)

Abstract: Potent antiviral activity against measles, influenza and polio viruses was observed in the hemolymph of Lonomia obliqua. The antiviral protein responsible for this activity was isolated, purified by gel filtration chromatography using a gel filtration column system (Superdex 75) and further fractionated using a Resource-Q ion exchange column system. Experiments with the purified protein led to a 157-fold reduction (from 3.3+/-1.25 x 10(7) to 2.1+/-1.5 x 10(5) TCID(50)mL(-1)) in measles virus production and a 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 33 publications
3
19
0
5
Order By: Relevance
“…On the other hand, extracts of egg wax of A cajennense led to a 256-fold reduction in picornavirus production by L929 cells. These results are in conformity to those obtained with hemolymph of Lonomia obliqua (Greco et al 2009). The present data suggest that the eggs wax of A. cajennense can be an important source to obtain products with antiviral or antimicrobial activity.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…On the other hand, extracts of egg wax of A cajennense led to a 256-fold reduction in picornavirus production by L929 cells. These results are in conformity to those obtained with hemolymph of Lonomia obliqua (Greco et al 2009). The present data suggest that the eggs wax of A. cajennense can be an important source to obtain products with antiviral or antimicrobial activity.…”
Section: Discussionsupporting
confidence: 79%
“…In special, the control of viral infections is of great interest in Public Health, and for this reason the development of new and better antiviral compounds is vital and desirable. The presence of a potent antiviral activity against measles, influenza and polioviruses in the hemolymph of caterpillar Lonomia obliqua has been previously shown (Greco et al 2009). Experiments with the purified protein led to a 157-fold reduction in measles virus production and a 61-fold reduction in polio virus production.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Souza et al [88] purified an anti-apoptotic protein from L. obliqua hemolymph of about 51 kDa. This protein was able to prevent apoptosis in Sf-9 cell culture induced by nutrient deprivation and by actinomycin D. Recently, Greco et al [89] reported the presence in hemolymph of a potent antiviral activity against human virus in vitro. Apparently, this molecule has a molecular mass of approximately 20 kDa.…”
Section: Lonomia Obliqua Toxins Affecting Cellular Survival and Deathmentioning
confidence: 99%
“…However, baculovirus infection induces oxidative stress and cell death, which limits recombinant protein production (Vieira et al 2006). Recently some studies have demonstrated the presence of pharmacologically active substances in hemolymph of Lonomia obliqua, which can enhance Sf-9 insect cell growth and culture longevity (Maranga et al 2003;Raffoul et al 2005;Souza et al 2005;Mendonça et al 2008;Greco et al 2009). In the present work, hemolymph (whole extract or a semi-purified fraction) was applied to improve BEVS/IC system by increasing rotavirus recombinant protein.…”
Section: Introductionmentioning
confidence: 99%